Optimization of bacterial bioaugmentation for groundwater Mn removal using a waste-based culture medium and lyophilization - Ciancio Casalini, Lucila (2020)
Water Impact StatementBioaugmentation for groundwater Mn removal has been performed with fresh bacterialinoculums. Lyophilized inoculums will solve the problems of keeping bacteria viableand transporting large culture volumes. Growing the inoculum in organic waste offersthe possibility to replace expensive culture media and to re-use industrial waste. Thesenew technologies will optimize bioaugmentation processes applicable to Mngroundwater full-scale biofiltration.